2010
DOI: 10.3390/ijms11114348
|View full text |Cite|
|
Sign up to set email alerts
|

Myricetin Protects Cells against Oxidative Stress-Induced Apoptosis via Regulation of PI3K/Akt and MAPK Signaling Pathways

Abstract: Recently, we demonstrated that myricetin exhibits cytoprotective effects against H2O2-induced cell damage via its antioxidant properties. In the present study, myricetin was found to inhibit H2O2-induced apoptosis in Chinese hamster lung fibroblast (V79-4) cells, as shown by decreased apoptotic bodies, nuclear fragmentation, sub-G1 cell population, and disruption of mitochondrial membrane potential (Δψm), which are increased in H2O2-treated cells. Western blot data showed that in H2O2-treated cells, myricetin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 30 publications
5
66
0
Order By: Relevance
“…p38 MAPK signaling pathway was a prominent factor on regulating cell apoptosis, immune, and inflammatory responses through its positive regulation on the posttranscriptional control of TNF-α and the cytokine expression under stress conditions, including I/R injury [28][29][30]. I/R injury is a common pathological condition that could cause acute inflammatory reaction, severe MOF, and even mortality [31].…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK signaling pathway was a prominent factor on regulating cell apoptosis, immune, and inflammatory responses through its positive regulation on the posttranscriptional control of TNF-α and the cytokine expression under stress conditions, including I/R injury [28][29][30]. I/R injury is a common pathological condition that could cause acute inflammatory reaction, severe MOF, and even mortality [31].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that protective pharmacological substances such as anthocyanins, cumarin, myricetin, quinones, tannins, carotenoids, and flavonols from fruit of higher plants absorb incident light at specific wavelengths, offering a spectral range for fluorescence excitation (Kang et al 2010;Merzlyak et al 2008;Yip et al 1993;Rost 1995). Although the screening of natural plant extracts has shown that plant fruits bear a great potential for new fluorescent compounds or fluorophores (Buschmann et al 2000;Goodwin 1953), little attention has been paid to these inexpensive natural products in microbiology, including mycology.…”
Section: Introductionmentioning
confidence: 98%
“…One such stain is lactofuchsin (Carmichael 1955), used as a mounting medium and staining agent for studying fungi. Although the lactofuchsin mixture binds well to the cell walls of fungi, its toxicity negatively impacts certain Zygomycota, Ascomycota, and Basidiomycota strains (Bragulat et al 1991;Chau et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A. Myr has a variety of pharmacological effects, including anti-bacterial (8), analgesic (8), anti-tumor (9,10), anti-allergic (11)(12)(13), anti-oxidant (14,15), blood sugar-lowering (16) and hepatoprotective actions (17). It also exerts protective effects against cardiovascular diseases, including atherosclerosis (18), ischemia-reperfusion injury (19), myocardial infarction (20) and hypertension (21,22).…”
Section: Introductionmentioning
confidence: 99%